Penentuan kriteria ekonomi sirkular dan keberlanjutan dalam pemilihan suplier pada rantai pasok pangan menggunakan fuzzy demantel approach - Ira Aprilia; Dwi Iryaning Handayani; Ahmad Izzuddin; Iffan Maflahah (AGROINTEK, 2024)
This research aims to determine the criteria for CE and sustainability as indicators for evaluating suppliers in the food supply chain. This study is beneficial in realizing government regulations on environmentally friendly products. The method used in this research combines fuzzy multi-criteria decision making theory and the Dematel technique, known as Fuzzy Dematel. The criteria for CE and sustainability in the food supply chain suppliers in this study are obtained from literature and Expert’s opinions, consisting of 20 criteria distributed across four aspects: economic, environmental, social, and circular. The criteria that have a strong influence and relationship with CE and sustainability criteria in the evaluating  food supply chain suppliers are cost, design of products, and the use of recyclable materials in packaging products. This indicates that these criteria are the most important factors that can have a significant influence as indicators for selecting CE and sustainability suppliers. With these criteria, managers can assist in evaluating supplier in industries undergoing a transition toward a CE.